Detection of nucleotide disbalance in cells undergoing oncogene-induced senescence - Nikiforov, Mikhail A. (Methods Mol Biol, 2017)
DNA damage response has been characterized as an important mediator of senescence phenotypes induced by activated oncogenes in normal human cells. Depletion of intracellular deoxyribonucleotide pools has been recently recognized as one of the major causes for DNA damage in these cells. Cells undergoing oncogene-induced senescence display decreased expression of several rate-limiting enzymes involved in the biosynthesis of deoxyribonucleotides, including thymidylate synthase (TS) and ribonucleotide reductase (RR). Individual depletion of these enzymes leads to premature senescence. Reciprocally, ectopic expression of TS and RR or addition of deoxyribonucleosides resulted in suppression of senescence phenotypes in normal or tumor cells caused by overexpression of activated HRAS or depletion of C-MYC, respectively. Therefore, in the current chapter, we will describe the methodology for the quantitative measurement of nucleotide pools in senescent cells.